First report of surgery for anencephaly in twin pregnancies: Technical notes and postoperative management. Issue 12 (24th March 2023) - Menekşe, Güner; Kahvecioğlu, Dilek; Aksoy, Hatice Tatar; Kankaya, Yüksel; Bayar, Mehmet Akif
Abstract : Anencephaly, the most severe form of neural tube defect, has no known cure, and in most cases, patients die before or shortly after birth. To date, no surgical intervention has been reported in the management of anencephaly. This study presents a case of dichorionic-diamniotic twin pregnancy in which 1 twin was anencephalic and describes the surgical management of this complex case. We aimed to share the problems experienced during the follow up of a patient who survived for a long time after surgery. We also aimed to highlight several clinical issues, including the challenges of managing anencephaly in twin pregnancies, problems experienced during the follow up process in our case, diagnosis of brain death in anencephaly cases, and ethical dilemmas related to organ donation. This case is notable because of the challenging nature of the surgical procedure and complexity of postoperative care. By highlighting the difficulties encountered during the follow up period, we hope to provide insights to health professionals that can inform the management of similar cases in the future.